Case report and narrative review of the literature: a rare colonic stent failure in a palliative patient - Bressington, Morgan; O’Connor, Alexander; Telford, Karen (Frontiers in Gastroenterology, 2023)
Introduction With palliative patients, a holistic approach is important. Interventions should minimise length of hospital stay, maximise quality of life, and control symptoms. A self-expanding metal stent (SEMS) for the palliative treatment of malignant large bowel obstruction (MLBO) is designed to provide these benefits to patients approaching the end of their life. We present the case of a patient treated with a SEMS over 2 years earlier for MLBO. He was treated with palliative intent at diagnosis because his frailty and medical co-morbidities precluded surgery. He later presented with severe tenesmus, and these new symptoms were later found to be due to a rare stent failure in which the stent had fractured and was irretrievable. This had to be managed conservatively before the patient sadly passed away 7 months later. Discussion A SEMS is considered the first-line treatment to relieve MLBO caused by inoperable left-sided colonic cancer. This treatment offers a reduced length of hospital stay, reduced stoma rates, fewer complications, and comparable survival compared to de-functioning stoma. However, SEMSs are not expected to be in use for extended periods of time. The literature reports an average survival after a colonic stent insertion of between 121 and 199 days when used in a palliative setting. Conclusion This is one of the first case reports to describe a colonic stent failure occurring over 2 years after insertion. This case argues that further research into the longer-term outcomes of this management option is warranted, particularly as palliative patients are living longer.